India's policy towards South Pacific: Expanding horizons of the Indo-Pacific region. (3rd July 2019) - Jha, Pankaj
ABSTRACT: For India, the concept of Indo-Pacific spans from the East Coast of Africa to the Western Pacific. This is because for India, it is the outer limit of the Indo-Pacific, and South Pacific acts as the new periphery of its Act East policy. Many ASEAN nations are deliberating about the utility of the Indo-Pacific. In the past, the then Indonesia Foreign Minister Marty Natalagewa had proposed the Indo-Pacific treaty and in 2019, ASEAN discussed the new geo-strategic construct despite variations in the approach and subscription. For India, South Pacific has three major objectives catering to its Act East policy; its need for supporting votes for its Security Council permanent member seat, Indian diaspora in the region, and harnessing sea bed mineral resources with island nations under the blue economy concept. However, whether India does have the desire or is just scouting for resources and therefore wants to protect its strategic interest across the Indo-Pacific region needs further scrutiny. India's approach with regard to Indian Ocean has been appreciated but now it is using Act East policy to encapsulate South Pacific region through its Oceania approach. The paper discusses strategic and functional aspects of India's approach.